1999
DOI: 10.1111/j.1469-7793.1999.151af.x
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine receptor subtypes and vasodilatation in rat skeletal muscle during systemic hypoxia: a role for A1 receptors

Abstract: It is widely accepted that adenosine is released within tissues under hypoxic conditions. Accordingly, several studies in which adenosine receptor antagonists or adenosine deaminase have been used indicate that locally released adenosine makes important contributions to the respiratory and cardiovascular responses that are induced by systemic hypoxia. For example, adenosine has been shown to contribute to the central respiratory depression of systemic hypoxia, by actions within the brain, and to play a part in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

33
181
5

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(219 citation statements)
references
References 26 publications
33
181
5
Order By: Relevance
“…Previous studies on the influence of adenosine on the splanchnic circulation, including the pancreas, have unequivocally demonstrated that the vasodilating effects are mediated by A 2 receptors (18,24). However, a vasodilator response mediated by A 1 receptors exists in other vascular beds, e.g., the diaphragm (14) and other skeletal muscle (8,9,38).…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies on the influence of adenosine on the splanchnic circulation, including the pancreas, have unequivocally demonstrated that the vasodilating effects are mediated by A 2 receptors (18,24). However, a vasodilator response mediated by A 1 receptors exists in other vascular beds, e.g., the diaphragm (14) and other skeletal muscle (8,9,38).…”
Section: Discussionmentioning
confidence: 93%
“…Because 4 subtypes of adenosine receptors have been cloned in the rat, 9,10 we used specific antagonists for subtypes of adenosine receptors: DPCPX for A1 adenosine receptors, A2a for SCH58161, A2b for MRS1754, and A3 for MRS1523. 20,[22][23][24][25]35 We found that the improvement in cardiac performance by long-term stimulation by CADO was blunted by MRS1754 but not by the antagonist of other subtypes of adenosine receptors. To the best of our knowledge, this study was the first to demonstrate the involvement of adenosine A2b receptor in cardiac remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Both cell types have been reported to possess A1, A2 A , and A2 B membrane receptor subtypes (37). ADO receptors have been shown to cause vasodilation through NO-dependent processes and K ATP channels (8,23,33), although the exact location of the K ATP channels (endothelial cells or smooth muscle cells) is unknown. ADO receptors on smooth muscle cells have been shown to facilitate vasodilation through cAMP/protein kinase A-dependent mechanisms, resulting in the opening of K ATP channels, presumably on smooth muscle cells, and the resulting hyperpolarization will cause vasodilation (for review, see Ref.…”
Section: Vasodilators Implicated In the Dilatory Response To Muscle Cmentioning
confidence: 99%
“…Vascular cell NOS is involved in the dilatory pathways for other vasodilators implicated in muscle contraction such as ACh and ADO (8,23), and L-NAME application may, therefore, also be blunting the dilatory response imposed by these dilators during contraction. Although we did not test the contribution of ACh in this study, we did test the contribution of ADO.…”
Section: Vasodilators Implicated In the Dilatory Response To Muscle Cmentioning
confidence: 99%